Fluid Dynamics Conference 1994
DOI: 10.2514/6.1994-2317
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of vortical structures in the shear-layer of delta wings

Abstract: The dcvelopment of the leading-edge vortex flow on dclta wings with emphasis on the three-dimensional scparated shear layer and the stationary, streamwise vortical structures that appear has been experimentally investigated. Flow-field velocities and pressures were obtaincd through five-hole probe measurements for three wing swceps and several angles of attack and Reynolds numbers ranging from 500,000 to 1,250,000. Two volumetric data sets were obtained above one planform at two angles of attack, allowing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…They include Squire et al, 10 Gad-el-Hak and Blackwelder, 11,12 Payne et al, 13 Lowson, 14 and Reynolds and Abtahi. 15 Further, time-averaged quantitative characterizations of vortical substructures involve the work of Verhaagen et al, 16 Washburn and Visser, 17 Lowson et al, 18 Riley and Lowson, 19 and Mitchell et al 20 The occurrence of vortical substructures was first computed by Gordnier and Visbal 21,22 who demonstrated their existence in the absence of external forcing. Mitchell et al 23 and Mitchell and Molton 24 also have computed patterns of vortical substructures using a different numerical approach.…”
Section: B Flow Structure On Highly Swept Wingsmentioning
confidence: 99%
“…They include Squire et al, 10 Gad-el-Hak and Blackwelder, 11,12 Payne et al, 13 Lowson, 14 and Reynolds and Abtahi. 15 Further, time-averaged quantitative characterizations of vortical substructures involve the work of Verhaagen et al, 16 Washburn and Visser, 17 Lowson et al, 18 Riley and Lowson, 19 and Mitchell et al 20 The occurrence of vortical substructures was first computed by Gordnier and Visbal 21,22 who demonstrated their existence in the absence of external forcing. Mitchell et al 23 and Mitchell and Molton 24 also have computed patterns of vortical substructures using a different numerical approach.…”
Section: B Flow Structure On Highly Swept Wingsmentioning
confidence: 99%
“…It is interesting to note that the substructures follow a helical trajectory around the vortex core and the spacing (frequency) between the substructures appears relatively constant, confirming the observations of Washburn and Visser. 17 Additionally, the substructures remain coherent even in the post-breakdown region of the flowfield. There are some discontinuities in the results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…secondary vortices. 10 ,20 Washburn and Visser 17 suggested the substructures are generated by nonviscous instabilities in the shear layer and that their formation is governed by the transverse flow of the leading-edge vortices. Yet another hypothesis postulates that a longitudinal instability associated with the curvature of the separating shear layer is at the origin of the substructures.…”
Section: Introductionmentioning
confidence: 99%
“…Once it is initiated, this interaction process no longer requires external perturbations to sustain it. At present, the exact triggering source for our experiments is not clear, although we suspect that inherent disturbances from the experimental setup (the vibration of the water towing tank facility) might be responsible, as another study 15 has suggested. Hubner and Komerath 16 have studied the quasi-periodic velocity uctuations over a delta wing and showed the existence of uctuating energy within a narrow frequency bandwidth.…”
Section: Reconnection Of the Primary Vortex And The Shear Layermentioning
confidence: 94%